2017
DOI: 10.3329/ajmbr.v3i2.33580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yoga on flexibility and balance: a quasi-experimental study

Abstract: Despite having number of health benefits, yoga also has a proven role in enhancing performance of athletes boosting specific components of fitness. Our aim was to study the effect of yoga on flexibility and balance among shooting trainee athletes at BKSP, Bangladesh. A quasi-experimental study was conducted among shooting trainee athletes. In total 20 athletes took part in this study. In each group we had 10 participants (10 in yoga group and other 10 in non-yoga group). Regular yoga session have been conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…1721 The specific and familiar example of Yoga has been used amongst many international football, rugby, cricket, and golf clubs including countries such as New Zealand, United States of America (USA) and South Africa (SA). 22 Yoga is a highly structured activity that can simultaneously enhance several specific components of fitness. Similarly, to rhythmic movement, Yoga incorporates music and movement, allowing the muscles, tendons, and ligaments to move through a full range of motion.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1721 The specific and familiar example of Yoga has been used amongst many international football, rugby, cricket, and golf clubs including countries such as New Zealand, United States of America (USA) and South Africa (SA). 22 Yoga is a highly structured activity that can simultaneously enhance several specific components of fitness. Similarly, to rhythmic movement, Yoga incorporates music and movement, allowing the muscles, tendons, and ligaments to move through a full range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…22 Furthermore, it mimics critical aspects of athletic performance, such as flexibility, muscular strength and endurance as well as co-ordination. 22 A 10-week preliminary study on the impact of Yoga on specific aspects of athletic fitness amongst soccer players indicated that the group who practised Yoga, demonstrated improvement in both flexibility and balance. 23 Moreover, to emphasise how rhythmic movement contributes to other sports, can be seen in the following examples: co-ordination and isolation aspects helps with sports such as swimming and improved dynamic balance assists in sports such as gymnastics and track and field events.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations